INTEGRASI ETNOPEDAGOGI: TRANSFORMASI KEARIFAN LOKAL PERTANIAN DESA POJOK KABUPATEN KARANGANYAR SEBAGAI SUMBER BELAJAR KONTEKSTUAL - Sabrina Kartika Putri; Dwi Anggraeni Siwi (STKIP Subang, 2026)
This study aims to analyze the process of ethnopedagogy integration through the transformation of local agricultural wisdom in Pojok Village as a learning resource for Natural and Social Sciences (IPAS) for fourth graders, as well as teacher strategies in overcoming obstacles to its implementation at Pojok 01 Public Elementary School. This study used a qualitative method with a case study design, with subjects consisting of fourth-grade teachers and fourth-grade students. Data collection techniques included participatory observation, in-depth interviews, and documentation. Interactive data analysis was used as an analytical technique. The results showed that the curriculum transformation was carried out by synchronizing local agrarian wisdom, which was originally oral, into formal project-based teaching modules. Field learning applied the philosophical principle of